Intraspecific Variation and Palaeogeographic Dispersal of the Mississippian Miospore Reticulatisporites magnidictyus Playford & Helby, 1968 - Playford, Geoffrey (Palynology, 2018)
Renewed study of an Australian Mississippian-age palynoflora — the Grandispora maculosa zonal assemblage from the Mount Johnstone/Italia Road Formation (Hunter Valley, New South Wales) — reveals significant morphological variation in some of its key miospore components — in particular Reticulatisporites magnidictyus, the subject of the present account. Detailed microscopy of numerous topotypic specimens of this species, originally described in 1968, results in its formal emendation; this takes particular account of the hitherto unrecognised presence of a proximo-apical prominence about the confluence of the laesurae. The G. maculosa palynoflora, with its constituent R. magnidictyus, has been reported from within a ca. 30–45°S palaeolatitudinal belt, at numerous Western, Eastern, and Northern Gondwanan locations in strata of middle Visean—early Serpukhovian age, but with a possible extension into the Early Pennsylvanian (Bashkirian). Consequently, R. magnidictyus is one of a very limited group of distinctive miospore species that facilitate long-distance chronostratigraphic correlation within the supercontinent.